The Effects of Horizontal and Exchange Inequity on Tax Reporting Decisions - Moser, Donald V.; Evans, John H.; Kim, Chung K. (The Accounting Review, 1995)
[A general prediction from the economic theory of tax reporting is that taxpayers will report more income as the tax rate increases, but the related empirical evidence has been mixed. We conducted an experiment to examine whether taxpayers' responses to a tax-rate change depend on both economic effects and perceptions of horizontal and exchange inequity. Our findings reconcile the previously inconsistent empirical results by identifying conditions under which perceptions of inequity drive taxpayers' reporting decisions. In summary, subjects reported less (more) income as tax rates increased (decreased) when they were inequitably treated relative to others, but not when they were equitably treated relative to others.]